Rotational motion of polyanion versus volume effect associated with ionic conductivity of several solid electrolytes - Zhao, Qian; Pan, Li; Li, Yuan-Ji; Chen, Li-Quan; Shi, Si-Qi (Rare metals, 2018)
Volume effect has been extensively investigated in several families of solid electrolytes, i.e., expanding the skeleton lattice by bigger-size substitution favors the ionic conduction. However, this effect is not applicable in α-Li 2 SO 4 and α-Na 3 PO 4 based inorganic ionic plastic crystal electrolytes, a unique family of solid electrolytes. Here, it is proposed that the underlying rotational motion effect of polyanion, which is actually inhibited by the substitution of bigger-size polyanion in single-phase solid solution region and causes the unexpected lowering of the ionic conductivity instead, should need the more consideration. Furthermore, through utilizing the rotational motion effect of polyanion, it is given that a new explanation of the ionic conductivities of Li 10 MP 2 S 12 (M = Si, Ge, Se) electrolytes deviating from the volume effect. These results inspire new vision of rationalization of the high-performance solid electrolytes by tuning the rotational motion effect of polyanion.